Unit Ultrafiltrasi-Karbon Aktif-Resin Penukar Ion Terintegrasi untuk Pengolahan Air Sumur Menjadi Air Minum - Putu Teta Aryanti; Tania Finarianingrum; Annisa Rakhmawati Darlis; Fahmi Widjaya; Adhani Nur Fajrina5 (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2021)
The availability of healthy well water is still become a problem in several areas in Indonesia, including Cimahi City, West Java. In general, the well water is treated using sand filter and adsorbent (either activated carbon or zeolite). However, the conventional methods produced unsafe drinking water, which does not meet drinking water standards. This study proposed integrated polysulfone ultrafiltration (UF), activated carbon (KA), and ion exchange resin (IE), as an alternative technology. The UF membrane provided a permeate flux of 42 L.m-2h-1. Based on Hermia’s model, the fouling was dominated by total and standard fouling with R2 values of 0.8989 and 0.8952, respectively. During the 2 (two) hours of filtration, the permeate flux decreased by 19%. Based on data from the analysis of water products, the UF-KA unit reduced hardness, organic matter, iron, and other contaminants to below the threshold value for drinking water quality standards. However, the concentration of manganese compounds was still 0.601 mg/L above the standard threshold (0.4 mg/L). With the addition of the IE unit after the UF-KA process, the water products produced meet the drinking water quality standards. The removal of turbidity, iron, and manganese by the UF-KA-IE was 95.9%, 99.9%, and 72.5%